2017
DOI: 10.1016/j.joca.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The association of pre-operative body pain diagram scores with pain outcomes following total knee arthroplasty

Abstract: Objective Approximately 20% of total knee arthroplasty (TKA) recipients have suboptimal pain relief. We evaluated the association between pre-surgical widespread body pain and incomplete pain relief following TKA. Method This prospective analysis included 241 patients with knee OA undergoing unilateral TKA who completed questionnaires preoperatively and up to 12 months post-operatively. Questionnaires included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scale and a body pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 30 publications
1
40
1
Order By: Relevance
“…Hawker et al 20 concluded that while a single TKA might substantially improve pain if the replaced joint is the main contributor to the patient's pain experience, the presence of arthritis in other joints and/or comorbid conditions would likely attenuate the overall effect of TKA on functioning. Dave et al 21 agreed with this hypothesis, reporting that more widespread body pain was associated with a higher likelihood of reporting 12-month WOMAC pain score >15 and a greater likelihood of failing to achieve the minimal clinically important difference in pain levels. They concluded that widespread pain as captured by the pain diagram, along with the pain catastrophizing score, may help identify persons with suboptimal TKA outcome.…”
Section: Painmentioning
confidence: 82%
“…Hawker et al 20 concluded that while a single TKA might substantially improve pain if the replaced joint is the main contributor to the patient's pain experience, the presence of arthritis in other joints and/or comorbid conditions would likely attenuate the overall effect of TKA on functioning. Dave et al 21 agreed with this hypothesis, reporting that more widespread body pain was associated with a higher likelihood of reporting 12-month WOMAC pain score >15 and a greater likelihood of failing to achieve the minimal clinically important difference in pain levels. They concluded that widespread pain as captured by the pain diagram, along with the pain catastrophizing score, may help identify persons with suboptimal TKA outcome.…”
Section: Painmentioning
confidence: 82%
“…34 Preoperative widespread pain was associated with more pain after TKA and failure to achieve relief from pain as defined by a minimal clinically significant difference after 12 months. 35 Surgeons should understand their patients and determine an indication for TKA to prevent persistent severe postsurgical pain.…”
Section: Discussionmentioning
confidence: 99%
“…TKA structural efficacy rates were derived from data in a study by Paxton and colleagues . TKA pain decrements were derived from 2 longitudinal studies in patients with knee OA undergoing TKA: the Adding Value in Knee Arthroplasty (AViKA) study and the Study of Total Knee Arthroplasty Responses (STARs) (see Supplementary Appendix Section a and Supplementary Table , available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr23716/abstract).…”
Section: Methodsmentioning
confidence: 99%